Proses Kebermaknaan Hidup Remaja Yang Menikah Di Usia Dini - Kusumaningtyas, Anggit, Setia Asyanti S.Psi., M.Si (2016)
Early Marriage is defined as the marriage done during adolescent period. Emotion in the period of adolescent is very unstable due to the inconsistency thought of the person. The adolescents should play role as adult and carry out the adult responsibiliy that should not be done by them immediately. Therefore, the adolescents will interpret their new life as something simple. The purpose of this study was to describe the process of seeking meaningfulness life of adolescent married in early age. The informants of this study have met the characteristics such as: a) female b) adolescents married in early age, as stated according to the Child Rights Act that child;s age is from 10-18 years old c) married for ± 1-3 years. The method applied in this study was a structured interview and observation. The results indicated that, the life purpose of adolescent married in early age is more modest than the marriage of adult age, such as to get more attention and has desire to prove that they can manage family in early age. Those life purpose can be reach by the three informants in different ways. The purpose of life the the are arcieved the three informants with a different way. The porpose of life could be arcived by looking for meaningfulness life. The process of teens who married early because the incident pregnancy out of wedlock feel feelings of despair, anxious, guilt, and life are means. Judge to marry, become aware of have been a wife and mother for his son, responsibility on the their obligantion, but from all informants did not have the initiave to expland their personal. They felt a meaningfullness life if coult happy parent, life in enough. Life in enough, and could live on their own. Happiness expected informants not all achieved because not happy parent, careless, need nenough and live on their own.